Application of Magnetic Carbon Nanocomposite from Agro-waste for the Removal of Pollutants from Water and Wastewater - Jayanthi, Barasarathi; Palsan Sannasi, Abdullah; Emenike Chijioke, Uche (Elsevier Ltd., 2022)
Water pollution has significant impact on water usage, and various contaminants, such as organic and inorganic compounds, heavy metals, dyes, pharmaceuticals compounds, pathogens and radioactive compounds, are implicated. The quest for globalisation, structural developments and other related anthropogenic activities promote the release of contaminants that induce water pollution. Hence, treatment and remediation options that can remove pollutants from watercourses and wastewater have been developed. Applied nanotechnology using carbon nanocomposites has recently drawn attention because it has the advantages of low preparation cost, high surface area, pore volume and environmental stability. Magnetic carbon nanocomposites usually exhibit excellent performance in adsorbing contaminants from aqueous solutions, and thus expanding the use of nanotechnology in water treatment is of great importance. Therefore, this review explores the geographical outlook of water pollution, sources of water pollution and types of contaminants found in water and discusses the use of carbon nanocomposites as an emerging sustainable technology for water pollutant removal. The various properties of carbon-based composites influence the extent of pollutant adsorption during water treatment processes. Most carbon-based nanocomposites are generated from biomass produced by agro-waste materials. Magnetic activated carbon nanocomposites produced from walnut shells and rice husk waste can remove 78% of Cd(II) from contaminated aqueous systems. Magnetic nanocomposites from peanut shell, tea waste, curcumin nanoparticles, sunflower head waste, rice husk, hydrophyte biomass, palm waste and sugarcane bagasse facilitate hydrothermal carbonisation, chemical precipitation, co-precipitation, chemical activation, calcination and fast pyrolysis. These nanocomposites have benefitted wastewater treatment by increasing efficiency in removing pharmaceutical, dye and organic contaminants, such as promazine, ciprofloxacin, amoxicillin, rhodamine 6G, methyl blue, phenol and phenanthrene. Hence, this review discusses the relatively low costs, good biocompatibility, large surface-to-volume ratio, magnetic separation capability and reusability carbon materials and highlights the advantages of using magnetic carbon nanocomposites in the removal of contaminants from water or wastewater through adsorption mechanisms.